DIASPORA IN INDONESIA-CHINA RELATIONSHIP AT THE COMPREHENSIVE STRATEGIC PARTNERSHIP ERA - Muas, R. Tuty Nur Mutia Enoch (UI Scholars Hub, 2023)
Diaspora is a potential non-state actor as a driver of people-to-people connections between the country of origin and the country of residence. People-to-people connections are part of public diplomacy, increasing in importance with information and communication technology. Indonesia-China relations have existed for more than seven decades, experiencing dynamic ups and downs. Since the inauguration of the Strategic Partnership between Indonesia and China in 2005 and then in 2013, it has increased to become a Comprehensive Strategic Partnership, and bilateral and multilateral relations have tended to increase. Bilateral and multilateral relations have managed to grow. However, from the Indonesian side, there are still classic obstacles in the relations between the two countries, namely the suspicion of China's good intentions and the role of the Tionghoa (Chinese Ethnic Group). The Tionghoa is an Indonesian citizen but culturally is a part of the Chinese diaspora. Despite that, along with the rapid progress of China, the number of Indonesian citizens (WNI) and descendants of Indonesian citizens living and-/or settling in China is also increasing rapidly and can be categorized as the Indonesian diaspora. How can the Indonesian diaspora play a role in people-to-people connection to increase mutual understanding between the two nations and reduce suspicion? that is the subject of this article. This research uses a historical approach to look at the role played by the diaspora, especially the Indonesian diaspora in China, in helping to improve Indonesia-China diplomatic relations.